1980
DOI: 10.2337/diacare.3.4.535
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and Modification of the Accuracy of Determinations of Urine Glucose Concentration

Abstract: Studies were designed to assess the accuracy of urine glucose testing in a sample of juvenile diabetic subjects, and to determine the effects of a visual discrimination training procedure on the accuracy. In the first study, each of 81 juvenile-diabetic children was presented three prepared glucose solutions and asked to determine the glucose concentration using the 2-Drop Clinitest method. Results showed errors in 54.3% of the judgments, with greatest difficulty occurring with 1-g/dl concentrations. The major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

1981
1981
1990
1990

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 1 publication
0
9
0
1
Order By: Relevance
“…Determinations were most likely to be correct when either no glucose or large amounts of glucose had been added to the urtne. 25 Thus, although wegenerally ask our patients to monitor themselves by daily spot -checking of urtne, we realize that the information obtained has only limited value. For example, if a patient who generally does not spill glucose starts to do so consistently, something would appear to be wrong and the patient andjor physician should attempt to identify the problem and correct it as soon as possible.…”
Section: Briel Summary Of Prescribing Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Determinations were most likely to be correct when either no glucose or large amounts of glucose had been added to the urtne. 25 Thus, although wegenerally ask our patients to monitor themselves by daily spot -checking of urtne, we realize that the information obtained has only limited value. For example, if a patient who generally does not spill glucose starts to do so consistently, something would appear to be wrong and the patient andjor physician should attempt to identify the problem and correct it as soon as possible.…”
Section: Briel Summary Of Prescribing Informationmentioning
confidence: 99%
“…25 A given urtne glucose value can reflect a rather wide range of blood glucose concentrations. Renal thresholds for urtnary glucose spillage vary from person to person and may vary over time in the same person.…”
Section: Briel Summary Of Prescribing Informationmentioning
confidence: 99%
“…This should be available 24 hour/day, seven days/week. 6 Studies have demonstrated that urinary glucose measurements frequently do not correlate with blood glucose level.' Furthermore, during pregnancy, increased glomerular filtration causes a rise in glucose excretion which would make glycosuria less reliable as an indicator of blood glucose levels.…”
Section: The Patient and Family Members Should Become Familiarmentioning
confidence: 99%
“…Finally, the inherent sensitivity-specificity problems of urine test materials, coupled with client testing errors, reduce the value of urine testing as a data collection method. 9 The use of SBGM has accelerated as data supporting its advantages have been reported. Following Tattersall The growth of SBGM has also been enhanced by recent technological advances in reflectance meters, reagent strips and capillary sampling devices.…”
mentioning
confidence: 96%